Artgrispira platensis as Alternative Teraphy for Children with HIV-positive - Sekar Wulandari, Ayu Fitri; Irwanti, Gisda (The Journal of The Indonesian Medical Students Association, 2010)
Long term antiretroviral therapy can lead to children body change due to the abnormal fat accumulation, increased level of blood cholesterol and glucose, lipodystrophy, metabolic change, and increased risk of cardiovascular diseases. Arthrospira platensis is a kind of Cyanobacteria that is safe to consume. It has a high nutritional level and contain HIV-1 inhibitor substances. Arthrospira plantesos contains 70% of protein, vitamin B-12, B-carotene, minerals especially zinc, tocopherol, and a-linolenic acid. Besides, Arthrospira plantesis also contains sulfated hemopolisaccharide substance which is called calcium-spirulan like substance that acts as inhibitor of HIV-1 replication. Hence, Arthrospira plantesis is a potential therapy for children with HIV without disturbing their growth and development.ÃÂ Key word: Arthrospira platensis, children, positive HIV